Rede social da família de usuários de drogas : cuidado de enfermagem pelo processo clinical caritas - Pandini, Andressa (2012)
Drug use and abuse is currently one of the main social and public health problems worldwidewith deep consequences for users, their families and communities. Since drug abuse is a mental illness, interventions are similar to the process involving Psychiatric Reform in Brazilby which the promotion of alternative models centered on the community, social networks and family care are provided. Conviviality with the drug user may have a great impact on the family nucleus and depends on relationship quality among members, external and internal family characteristics, on the stage of the life cycle and on the social and cultural context in which it is inserted. Knowledge on the family that experiences the problem and an understanding of its behavior, feelings and meaning attributed to the experience are highly relevant. Current essay investigates the social network of the families that live together with alcohol and drug users and the nursing care towards them. The descriptive qualitative research, the case study, performed in Maringá PR Brazil was fore grounded on the theoretical referential of the clinical caritas process of Jean Watson's Transpersonal Care Theory. Ten families of drug users attended to at a health unit in the above-mentioned municipality participated in the research. The unit was selected owing to its above-average indexes of hospitalization and violence related to drug abuse. Data were collected between January and March 2012 through half-structured interviews, by Genograms and Ecomaps and from reports on the development of a home assistance practice with three families. Nursing care, fore grounded on Watson's clinical caritas process, was conducted. Data underwent content analysis, theme mode. Results revealed that conviviality with drug users is difficult due to their unforeseen behavior, the lack of acknowledgement by the family with regard to the problem status as illness, social isolation, and financial, physical and psychological load. The problems negatively impact the families' social network which becomes fragile with regard to friends, neighbors, support services and others. Genogram and Ecomap reveal that families are monoparental and/or expanded families, that the users are generally unemployed and have low schooling, and that the social network of the families is basically built by members of the extended family and by people linked by religious beliefs. The drug users' social network is made up of people who frequent the bar, the smoking site and CAPS-ad. Family care at home is centered on the intra and extra family fragilities and on the valorization of social networks as a support source to face problems and make harmonious the return to family conviviality. Care helped the families to deal with the world of drugs with the least pain. Life context and the families' social network of drug users should be understood so that a more adequate assistance could be provided. In fact, the above facilitates the process of reorientation of treatment and broadens the list of strategies towards rehabilitation and promotion of the family health.